Pelestarian Kesenian Tradisional Gambang di Desa Danau Lamo, Kecamatan Maro Sebo, Kabupaten Muaro Jambi - Elizabeth Christiana Putri; Kiswanto Kiswanto (YASIN, 2026)
Social change marked by the dominance of modern entertainment has reduced the living space of traditional arts, including the Gambang art form in Danau Lamo Village, Muaro Jambi Regency, thereby creating challenges for its continuity and preservation amid increasingly intense cultural competition. This study aimed to analyze strategies for preserving Gambang as a form of cultural adaptation in response to social change. A qualitative method with an ethnographic approach was employed and analyzed through the lens of Charles Darwin’s evolutionary theory, particularly the concept of struggle for existence. Data were collected through participant observation, in-depth interviews with key artists and members of the Komunitas Keluarga Seni (KKS), documentation, and literature study, and then analyzed thematically. The findings show that Gambang has been able to survive through intergenerational, family-based transmission; the role of key actors such as Datuk and Nyai as custodians of tradition; innovations in performance formats; and the use of technology as a medium for documentation and promotion. The shift in performance context from traditional social spaces to cultural events and festivals reflects an adaptive response to changes in the “cultural habitat” without eroding local identity and values. In conclusion, the preservation of Gambang is an adaptive and dynamic process that is strongly determined by the community’s capacity to respond to social change, and its implications underscore the importance of strengthening the role of local communities and leveraging cultural innovation as sustainability strategies for traditional arts in the modern era.